Large-Scale Periodic Gust Generation and Spectral Analysis Approach for Characterization and Evaluation - Berk Zaloglu; Oksan Cetiner (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
Generating a periodic continuous gust in a controlled manner and at sufficiently large scales for the gust encounter studies on MAV applications is a challenge. In order to achieve it a pitching and plunging flat-plate is utilized with aggressive motion profiles. A range of periodic functions in pitch and plunge axes are investigated for the motion of the gust generator. Significant and distinct vortices are measured with PIV in its wake. An in-depth spectral analysis of the velocity vector field of the wake is performed to investigate the generated gust characteristics since the aggressive motion profiles can produce uniform and/or weak gust characteristics. To obtain the cases that simulate large-scale transverse wind gusts in a quasi-sinusoidal pattern, the PIV results are evaluated by using auto- and cross-spectral density plots of the entire flow field at the wake, ensuring the consistency of the gust characteristics for future gust wing encounter studies. Four cases in which the flat-plate moves with the quasi-feathering condition provide gusts that are useful to employ in MAV gust studies.